2015
DOI: 10.1111/cas.12743
|View full text |Cite
|
Sign up to set email alerts
|

Histidine‐rich calcium binding protein promotes growth of hepatocellular carcinoma in vitro and in vivo

Abstract: We have recently shown that the histidine-rich calcium binding protein (HRC) promotes the invasion and metastasis of hepatocellular carcinoma (HCC). In the current study, we evaluated whether HRC may also affect the growth of HCC. We found that ectopic expression of HRC obviously enhanced proliferation and colony formation, while suppression of HRC exhibited inhibitory effects. Furthermore, we demonstrated that HRC promoted tumor growth in nude mice. These effects may result from the ability of HRC to upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Inhibition of ER stress prevented hepatic fibrosis by attenuating HSC activation ( Men et al, 2015 ). Our previous study showed that HRC promoted the growth of liver cancer by inhibiting ER stress-induced apoptosis ( Liu et al, 2015 ). However, the effect of HRC on ER stress in HSCs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of ER stress prevented hepatic fibrosis by attenuating HSC activation ( Men et al, 2015 ). Our previous study showed that HRC promoted the growth of liver cancer by inhibiting ER stress-induced apoptosis ( Liu et al, 2015 ). However, the effect of HRC on ER stress in HSCs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…4 ). It has been proved that HRC promotes growth of hepatocellular carcinoma in vitro and in vivo [ 59 ]. Furthermore, HRC also plays a significant role in myocyte differentiation and in anti-apoptotic cardioprotection against ischemia/reperfusion induced cardiac injury [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our KEGG research demonstrated the Calcium signal pathway referred to PCa (Figure 4). It has been proved that HRC promotes growth of hepatocellular carcinoma in vitro and in vivo (59). Furthermore, HRC also plays a signi cant role in myocyte differentiation and in anti-apoptotic cardioprotection against ischemia/reperfusion induced cardiac injury (60).Intriguingly, the cardiovascular system development, cardiac muscle development, and cardiac muscle hypertrophy were displayed in GO analysis (Figure 4).We speculated the whole eld of muscle, as the part of extracellular matrix component, may make a profound effect on the biological property of PCa.…”
Section: Discussionmentioning
confidence: 99%